2002
DOI: 10.1136/bjo.86.9.975
|View full text |Cite
|
Sign up to set email alerts
|

The use of surgical facemasks during cataract surgery: is it necessary?

Abstract: Aim: To assess whether facemask utilisation by the surgeon during cataract surgery has any effect on the bacterial load falling onto the operative site. Method: Prospective randomised masked study. Consent was obtained from 221 patients. Cases were randomised to wearing a new mask or not wearing any mask throughout the procedure. Blood agar settle plates were placed adjacent to the patient's head in the operative field. Duration of procedure was noted. Plates were incubated and read at 48 hours. Colony forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Staff entering or leaving the surgical area did not always use a mask. It has been shown that facemasks reduce bacterial contamination of the perioperative area, 12 although their effect on endophthalmitis rates are unknown.…”
Section: Intraoperative Theatre Practicesmentioning
confidence: 99%
“…Staff entering or leaving the surgical area did not always use a mask. It has been shown that facemasks reduce bacterial contamination of the perioperative area, 12 although their effect on endophthalmitis rates are unknown.…”
Section: Intraoperative Theatre Practicesmentioning
confidence: 99%
“…5 When prescribing oral tetracycline for the treatment of blepharitis in adult patients, it is important to advise on oral hygiene measures and on avoidance of sunlight to minimize staining of teeth. Patients should also be reassured that the stain may be removed with abrasive cleansing by dental surgeon.…”
mentioning
confidence: 99%
“…Wearing a surgical face mask for cataract surgery is recommended. 12 Wear a surgical mask that fully covers the mouth and nose when entering the operating room if an operation is about to begin or already under way, or if sterile instruments are exposed. The current article is a retrospective study, and as such is limited by the inherent problems of any retrospective study (eg, recall bias, reporting bias, etc).…”
mentioning
confidence: 99%